The letters of Benjamin Franklin and Jane Mecom - Franklin, Benjamin, 1706-1790 (Memoirs of the American Philosophical Society, 1950)
The delightful correspondence between Benjamin Franklin and his favorite sister, with an introduction and notes by Carl Van Doren. Franklin wrote more letters to Jane Mecom than he is known to have written to any other person, and as she emerges through these letters we understand the reasons for the esteem in which he held her. The letters cover a period of over sixty years, give new and intimate glimpses of Franklin and of the times, particularly in Philadelphia and Boston, and will enchant any reader of 18th century Americana. Originally published in 1950. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.